PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP HASIL BELAJAR FISIKA SISWA KELAS VIII SMP NEGERI 4 METRO SEMESTER GENAP TAHUN PELAJARAN 2013/2014 - Khotimah, Laela Ngasarotul; Partono, Partono (Jurnal Pendidikan Fisika, 2015)
The aims of this research is to find the effect of guided inquiry learning model on learning outcomes physics eighth grade students of SMP N 4 Metro semester of academic year 2013/2014. The sample was VIIID as VIIIF as a control class and experimental class were selected by cluster random sampling. The study design used was Posttest-Only Control Design and researchinstruments in the form of sheets of observations and questions. Technical analysis of the data use normality test, homogeneity, test the similarity of two average, and two different test average.The results showed  that the  improvement of learning outcomes learning physics class experiments using guided inquiry learning model is higher than the control class students. From the calculation, the value of t =  2.18 is higher than the value table = 2.02 at significance level α = 5%. Therefore, it can  concluded that the model of guided inquiry learning effect on learning outcomes physics eighth grade students of SMP N 4 Metro semester of academic year 2013/2014. The success of learning during the learning process using guided inquiry model of learning because students can more freely in finding the concept it self and can connect between the knowledge possessed by the results they found in the experiments, so that influenced on learning outcomes.